Beyond The Ballot: Analyzing The Failure of Female Legislative Candidates in Local Indonesian Politics - Tondang, Donita; Kotarumalos, Amir; Muhtar, Muhtar (Baileo: Jurnal Sosial Humaniora, 2023)
This study aims to analyze the factors contributing to the electoral failure of female legislative candidates from the Indonesian Democratic Party of Struggle (PDIP) in the 2019 local legislative election in Ambon. Using a qualitative case study approach, the research draws on in-depth interviews, party documents, and official election results. The findings reveal four interrelated factors. First, the party’s recruitment and cadre development processes were suboptimal, leading to inadequate political preparation for female candidates. Second, weak female political leadership within the party structure limited access to strategic resources and support. Third, the lack of prominent female figures diminished electoral appeal among voters. Fourth, the weak social base of the candidates contributed to low electability. The novelty of this study lies in its emphasis on internal party dynamics as a critical factor in enabling—or constraining—women’s success in local electoral politics. This research recommends systemic reforms in gender-responsive recruitment and capacity-building within political parties, as well as the strengthening of female leadership at the local level. These findings offer valuable insights for the development of social sciences and humanities, particularly in understanding power relations, political representation, and structural challenges facing women in Indonesian local politics.